Efficacy of Tramadol, Low Dose Ketamine and Ondansetron in the Management of Intra-Operative Shivering After Sub Arachnoid Block (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Shivering is a common problem faced by an anesthesiologist during per-operative period as well as in post-operative period.Objective: The present study was designed to observe the efficacy of tramadol, low dose ketamine and ondansetron in the management of intra-operative shivering after sub arachnoid block.Methodology: This single center, parallel, double blind randomized control trialwas conducted in the Department of Anaesthesia, Analgesia and Intensive Care Medicine at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2007 to June 2009 for a period of two (02) years.Patients undergoing surgery with Sub Arachnoid Block, patients with age range from 18 to 60 years, patients from both sexes and ASA class I and class II were selected as study population.After recruitment each subject was allowed to draw one card and grouped accordingly. Group T: Shivering was treated with tramadol. Group K: Low dose ketamine was used to manage shivering. Group 0: Ondansetron was injected for shivering. The patients was also monitored for complications like nausea, vomiting and respiratory depression (defined as respiratory rate